Complete the equation.
1 3/5 – 5/7 = 56 – 25 = __
Share
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
To complete the equation, we need to perform the calculations step-by-step.
1. Convert the mixed number (1 frac{3}{5}) to an improper fraction:
[
1 frac{3}{5} = frac{5 times 1 + 3}{5} = frac{5 + 3}{5} = frac{8}{5}
]
2. Now, we need to subtract ( frac{5}{7} ) from ( frac{8}{5} ). To do this, we need a common denominator. The least common multiple of 5 and 7 is 35. So we convert both fractions:
– For ( frac{8}{5} ):
[
frac{8}{5} = frac{8 times 7}{5 times 7} = frac{56}{35}
]
– For ( frac{5}{7} ):
[
frac{5}{7} = frac{5 times 5}{7 times 5} = frac{25}{35}
]
3. Now we can subtract:
[
frac{56}{35} – frac{25}{35} = frac{56 – 25}{35} = frac{31}{35}
]
4. Next, let